1994
DOI: 10.1177/156482659401500317
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Tool for Traditional Birth Attendants to Identify Low-Birth-Weight Infants

Abstract: One of the most important strategies in health development is inter-sectoral collaboration. This study is an example of collaboration between a medical doctor and an animalproduction scientist to develop an easy, low-cost, rapid method for the assessment of birth weight. In developing countries where neonatal and infant mortality are high, birth weight could be a useful measure for identifying high-rise; neonates who need special attention. However, weighing a newborn is often not possible because more than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
1
3
1
Order By: Relevance
“…The mean birth weight did not differ between male and female in this study, in contrast to other investigators which reported the different mean birth weight among male to female group. 15,19,20 Low birth weight in this study (6.3%) is less than reports by Alisyahbana (14%) 16 or Gazali (19.8%). 21 Of all the subjebts, no one is small for gestational age (SGA).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…The mean birth weight did not differ between male and female in this study, in contrast to other investigators which reported the different mean birth weight among male to female group. 15,19,20 Low birth weight in this study (6.3%) is less than reports by Alisyahbana (14%) 16 or Gazali (19.8%). 21 Of all the subjebts, no one is small for gestational age (SGA).…”
Section: Discussioncontrasting
confidence: 51%
“…Gozal and Sasanow noted MAC strongly correlated to birth weight, 10.12 Magzoub found ChC correlated well to birth weight. 15 Our present study found four anthropomoteric parameters correlated strongly to birth weight (r > 0.81), namely ChC, AC, CC and MAC with the highest correlation coefficient is noted for CC (r = 0.92, p < 0.001).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…The correlation of the various anthropometric parameters was made in comparison to weight as a constant. Hence the best predictor of the low birth weight can be made [3][4][5].…”
Section: Introductionmentioning
confidence: 99%